Motorcycle transport: a threat to road safety in a community in Sub-Saharan Africa. (7th October 2012) - Bello, J; Nasir, A; Solagberu, B; Ofoegbu, C; Abdur-Rahman, L
Abstract : Background: There is a noticeable increase in the use of motorcycles in our communities for commercial transportation. It has been reported that the risk of dying for every kilometre travelled from a motorcycle crash is 20 times higher than from a motor vehicular crash. Objectives: This study was done to determine the incidence and trend of Motorcycle Injuries (MCI) in our community. Methods: A prospective study of patients presenting with MCI at a University Hospital in Nigeria over a 3-year period was done using a structured questionnaire. Results: There were 432 MCI patients, 5 : 1 predominance of males over females, age range 3–80 years, median 30. The yearly incidence (morbidity n; mortality % of n) were (112, 7.0%), (158, 7.5%) and (162, 15.4%) for the first, second and third year respectively. Riders were (363, 84.1%) and pedestrians (69, 16.0%). Only one rider (0.3%) wore a helmet. Common Injuries sustained were extremities alone (168, 38.9%), head injuries alone (119, 27.5%), head and extremities (110, 25.5%). Twenty-four patients (5.6%) needed intensive care; all had head injury and about three-quarters died (p<0.05). Forty-five patients (10.4%) died overall, 91% of these were head injured and none had used a crash helmet. Significance: There is an increasing incidence of and mortality from MCI. Poor use of crash helmets and Head injuries is common amongst mortalities. There is need for education of riders and enforcement of helmet use.